Lack of Association Between Epicardial Fat Volume and Extent of Coronary Artery Calcification, Severity of Coronary Artery Disease, or Presence of Myocardial Perfusion Abnormalities in a Diverse, Symptomatic Patient Population. (March 2015) - Tanami, Yutaka; Jinzaki, Masahiro; Kishi, Satoru; Matheson, Matthew; Vavere, Andrea L.; Rochitte, Carlos E.; Dewey, Marc; Chen, Marcus Y.; Clouse, Melvin E.; Cox, Christopher; Kuribayashi, Sachio; Lima, Joao A.C.; et al.
<x xml:space="preserve">Abstract</x> Background— Epicardial fat may play a role in the pathogenesis of coronary artery disease (CAD). We explored the relationship of epicardial fat volume (EFV) with the presence and severity of CAD or myocardial perfusion abnormalities in a diverse, symptomatic patient population. Methods and Results— Patients (n=380) with known or suspected CAD who underwent 320-detector row computed tomographic angiography, nuclear stress perfusion imaging, and clinically driven invasive coronary angiography for the CORE320 international study were included. EFV was defined as adipose tissue within the pericardial borders as assessed by computed tomography using semiautomatic software. We used linear and logistic regression models to assess the relationship of EFV with coronary calcium score, stenosis severity by quantitative coronary angiography, and myocardial perfusion abnormalities by single photon emission computed tomography (SPECT). Median EFV among patients (median age, 62.6 years) was 102 cm3 (interquartile range: 53). A coronary calcium score of ≥1 was present in 83% of patients. Fifty-nine percent of patients had ≥1 coronary artery stenosis of ≥50% by quantitative coronary angiography, and 49% had abnormal myocardial perfusion results by SPECT. There were no significant associations between EFV and coronary artery calcium scanning, presence severity of ≥50% stenosis by quantitative coronary angiography, or abnormal myocardial perfusion by SPECT. Conclusions— In a diverse population of symptomatic patients referred for invasive coronary angiography, we did not find associations of EFV with the presence and severity of CAD or with myocardial perfusion abnormalities. The clinical significance of quantifying EFV remains uncertain but may relate to the pathophysiology of acute coronary events rather than the presence of atherosclerotic disease.